Detection of Rubella Virus-Specific Immunoglobulin G in Saliva by an Amplification-Based Enzyme-Linked Immunosorbent Assay Using Monoclonal Antibody to Fluorescein Isothiocyanate - Vyse, A. J. (American Society for Microbiology, 1999)
An immunoglobulin G (IgG)–capture enzyme-linked immunosorbent assay (ELISA) for rubella virus is described. The assay uses a fluorescein isothiocyanate (FITC)–anti-FITC amplification system. The detection limit of the ELISA was approximately 7 IU of rubella virus-specific IgG per ml of serum sample. For saliva samples the performances of the capture ELISA and previously described radioimmunoassay were assessed, and the results of those two assays were compared to the rubella virus-specific IgG result obtained by a commercial ELISA (Behring Enzygnost) with a panel of paired serum and saliva samples. This comparison showed that the capture ELISA with saliva was more sensitive than the radioimmunoassay and that the results correlated better with the serum IgG result than the results of the radioimmunoassay did, with an overall sensitivity of 82% and a rank correlation of 0.68, whereas the sensitivity and rank correlation for the radioimmunoassay were 74% and 0.45, respectively. For subjects of 10 years of age or younger, the ELISA with saliva had a sensitivity of 94% and a specificity of 100% compared to the results of the ELISA (Behring Enzygnost) for rubella virus-specific IgG with corresponding serum samples. The sensitivity was much lower for subjects ages 17 years or older. The assay may have wider epidemiological use with saliva specimens, particularly those from children.